Assessing the state of physical infrastructure in progressive urbanization strategy: SAP-LAP analysis. (July 2019) - Chavan, Meena; Chandiramani, Jyoti; Nayak, Sushma
Abstract: The paper examines the current trends in Indian urbanization, a country known to be the second most populous country in the world. It aims to explore whether India, with its prevailing urban physical infrastructure bottlenecks and targeted policies to overcome the same, is equipped enough to sustain a growing urban population. Due to the excessive concentration of population in cities, the link between urbanization and development has evolved as a critical concern for policy makers. The paper employs a situation-actor-process (SAP) - learning-action-performance (LAP) [SAP-LAP] model of inquiry to assess the state of urban physical infrastructure in India and indicates future actions necessary from the standpoint of reaching the Sustainable Development Goals (SDG) target of inclusive, consistent, sustainable and resilient infrastructure to bolster economic progress and social welfare, with an emphasis on affordable and even-handed access to all. There has been paucity of studies in the recent past which explore government's role in recognizing physical infrastructure as a sustaining factor to urbanization and its paradoxical policy response—excessive zeal on the one hand and extreme apathy on the other—to urban development issues. The SAP-LAP framework shall assist systemic exploration of various issues in India's urbanization, with specific emphasis on physical infrastructure. This holistic approach would enable to identify further actions to realize sustainable growth and livability benefits of urbanization for India.